Length-weight relationships and condition factor of Asian sheat catfish, Wallago attu (Bloch & Schneider, 1801) inhabiting different rivers of India - Graish Kumar; Ankur Kashyap; Mohammad Serajuddin (Journal of Fisheries, 2023)
Wallago attu is a freshwater catfish and has been classified as ‘Vulnerable’ in Red Data List of threatened species by IUCN. Length-weight relationship (LWR) of wild populations helps in understanding the pattern of fish growth that could be useful in fisheries management. The current work was carried out to the LWR and condition factor (K) of W. attu collected from five rivers of India (Ganga, Yamuna, Hooghly, Gomti and Pampa). A total of 261 fish specimens were sampled for LWR study. The value of b for the population of river Gomti (t=1.0312), Ganga (t=1.4109) and Yamuna (t=0.3365) was not significantly different from isometric growth (b=3) in Pauly’s t-test whereas the populations of Hooghly (t=10.3609) and river Pampa (t=3.4593) were significantly different (p<0.001) indicating positive allometric growth in the fish of rivers Hooghly and Pampa. Linear plot of log a over b resulted in straight line showed strong relationship. Low K value (K<1) indicated the poor health conditions of the fish in all five rivers. This study would provide information regarding the status of LWRs of W. attu in five rivers of India that could serve as a baseline data for future sustainable management and conservation of this vulnerable fish.